Liberalizing trade in energy services and domestic regulation: New approaches in mega-regionals? - Krajewski, Markus (Springer International Publishing, 2017)
In light of recent negotiations on mega-regional trade agreements this chapter analyses if and how such agreements approach the liberalization and regulation of energy services. In particular it discusses how liberalization commitments can be reconciled with regulatory principles and rules. In this regard, the chapter addresses the Transatlantic Trade and Investment Partnership (TTIP), the Comprehensive Economic and Trade Agreement (CETA) and the Energy Charter Treaty as a special case of a mega-regional agreement. It is shown that megaregionals have failed so far to deliver better and fairer results concerning energy services. As a consequence, renewed efforts to negotiate an agreement on energy in the multilateral trade system are called for.
CRIS-Team Scopus Importer:2023-03-21